Integrating Islamic values in geopolitical economy of development finance: Empirical evidence from OIC selected countries in the Asia-Pacific region - Syafrina Machfud; Imron Mawardi; Dahlia Bonang (Faculty of Islamic Economics and Business, UIN Salatiga, 2025)
Despite extensive literature on external debt and economic growth, the fiscal burden of multilateral debt service and its interaction with Islamic governance principles and multilateral development bank alignment remain empirically underexplored among Organization of Islamic Cooperation member states. This study examines the impact of multilateral debt service on GDP per capita growth across twelve OIC Asia-Pacific member states over 1996 to 2022, focusing on the moderating roles of governance quality, infrastructure investment, technological advancement, and Islamicity Index adherence. Applying System Generalised Method of Moments on an unbalanced panel of 312 country-year observations, results confirm a marginally significant negative short-run effect on growth through productive investment crowding out, with the long-run effect remaining negative and persistent. Infrastructure investment and technological advancement significantly mitigate these effects, while the Islamicity Index produces a marginally significant negative moderatingeffect in both horizons, reflecting structural constraints imposed by the prohibition of riba on conventional debt financing. New Asian Model banks demonstrate the most consistently positive growth outcomes, whereas Islamic-principled banks face persistent challenges reconciling debt obligations with Shariah requirements. These findings call for strategic integration of Shariah-compliant financing instruments, differentiated multilateral development bank engagement, and governance capacity investment across OIC member states